HOW CROWDS OF PEOPLE IN A RESTAURANT CAN BUILD THE RESTAURANT’S IMAGE AND IMPROVE CUSTOMER SATISFACTION? - Husna Ulinnuha; Budi Setiawan; Riyanti Isaskar; Agustina Shinta Hartati Wahyuningtyas (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Restaurant crowds are common these days, especially in popular restaurants. This is characterized by the number of visitors who want to eat at the restaurant. The crowd of a restaurant occurs because many people are enthusiastic and curious to visit the restaurant. The crowd of a restaurant can determine consumer behavior in the long run, and can even create an image of the restaurant. This study aims to examine the relationship between crowds, restaurant image, brand trust, brand attachment, and customer satisfaction. The data collection technique in this study was carried out using an online questionnaire (google form) distributed to 250 respondents who had visited a spicy noodle restaurant in Malang City. Data processing was carried out using the SEM-PLS (Structural Equation Modeling - Partial Least Square) method with WarpPLS 8.0 software. The results showed that the human crowding variable has a significant influence on restaurant image. In addition, restaurant image also significantly affects brand trust and brand attachment, and brand trust and brand attachment also significantly affect customer satisfaction. Based on the results of the study, business actors are expected to improve service quality, such as responsiveness in serving crowded restaurants so that later they can improve the image of the restaurant.